Benzo[1, 2-b:4, 5-b′]diselenophene-fused nonfullerene acceptors with alternative aromatic ring-based and monochlorinated end groups: a new synergistic strategy to simultaneously achieve highly efficient organic solar cells with the energy loss of 0.49 eV. Issue 19 (3rd May 2019) - Wan, Shi-Sheng; Xu, Xiaopeng; Wang, Jin-Liang; Yuan, Gui-Zhou; Jiang, Zhao; Ge, Gao-Yang; Bai, Hai-Rui; Li, Zheng; Peng, Qiang
Abstract : The PCE of 13.68% with the E loss of 0.49 eV were obtained, which were the highest values obtained to date in binary PSCs with monochlorinated NF-SMAs. Abstract : Herein, a new synergistic strategy using electron-rich core units and alternative aromatic structure-based 1, 1-dicyanomethylene-3-indanone (IC) end-groups for nonfullerene PSCs was reported and investigated in an attempt to simultaneously obtain excellent PCE with extremely low E loss . Specifically, two benzo[1, 2- b :4, 5- b ′]diselenophene-based, A–D–A-type chlorinated NF-SMAs (BDSeThCl andBDSePhCl ) were synthesized, which were linked with a new 2-chlorothienyl-based IC and a conventional monochlorinated phenyl-based IC as end-groups, respectively.BDSePhCl exhibited a wider and red-shifted absorption and downshifted energy levels thanBDSeThCl . The blend films ofBDSePhCl :PM7 exhibited better charge generation properties, more suitable phase separation, and more balanced charge mobilities as compared to those ofBDSeThCl :PM7 . Therefore, compared to theBDSeThCl :PM7 blends with the best PCE of 11.91% and the E loss of 0.58 eV, the optimalBDSePhCl :PM7 blends showed the enhanced PCE of 13.68% with the reduced E loss of 0.49 eV. Notably, the excellent PCE of 13.68% is the highest value recorded to date for A–D–A-type NF-SMAs with a monochlorinated IC group in binary PSCs. The E loss of 0.49 eV is the lowest value reported to date for A–D–A-type NF-SMAs in binary PSCs with the PCE > 13%. These results demonstrate that tailoring of the monochlorinated aromatic ring-based IC is an effective strategy to simultaneously improve the PCE and reduce the E loss in binary PSCs.